Optimization of YbBa2Cu3Oy Thick Film Formation on MgO Substrates using Yb2BaO5 and liquid phase. (September 2019) - Hattori, A.; Muralidhar, M.; Sai Srikanth, A.; Murakami, M.
Abstract: The production of best thick YbBa2 Cu3 Oy (Yb123) films on MgO substrates are crucial for the utilization of this technology in silver sheeted wire as similar to Bi-2223. In this work, in order to optimize YbBa2 Cu3 Oy films on MgO substrates, a mixture of alpha-terpineol and 2-ethyl acetate was utilized as a solvent to which 100 nm sized stoichiometric powder mixture of Yb2 BaO5, BaCuO2 and CuO was added and grinded for several hours to form a highly dense paste. Thick film precursors were prepared by spreading the paste over MgO substrates with a screen printing technique and various sintered and quench studies are done. Growth temperature is systematically varied between 800 and 950 °C for 30 minutes in air and quenched in liquid nitrogen. Similarly, sintering durations are varied systematically from 15 minutes to 8 hours. XRD reveals conformed that large Yb123 grains are formed when the thick films are sintered at 825 °C for 1 hour on MgO substrate. SEM micrographs are also in congruence with the XRD results depicting the giant Yb123 crystals. The present results clearly demonstrate that optimization of the growth temperature and time is crucial to obtain the large thick YbBa2 Cu3 Oy films on MgO substrates.